The knowledge, attitude and perception of HIV Voluntary Counseling and Testing (VCT) among young adults in Kempton Park community, north of Ekurhuleni Municipality, Gauteng Province : improving the uptake of VCT - Otasowie, E. D. (Stellenbosch : Stellenbosch University, 2017)
Thesis (MFamMed)--Stellenbosch University, 2010.